2015
DOI: 10.22495/jgr_v4_i3_p4
|View full text |Cite
|
Sign up to set email alerts
|

The impact of leadership styles on project success: Case of a telecommunications company

Abstract: Challenges within the customer service industry make leadership styles a key factor in the success of customer service project delivery. This research provides an overview of information and knowledge within a corporate environment with an underlying theme of defining leadership styles within the customer service projects environment to ensure successful project delivery. This research aims to investigate the perception of leadership styles required and factors that contribute to successful project delivery ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…exploitative leadership as a moderator to the relationship between project governance and ICT project success. There are studies in the past that focused on negative leadership styles and their impact on project performance (Lategan and Fore, 2015; Pircher Verdorfer et al. , 2019; Schmid et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…exploitative leadership as a moderator to the relationship between project governance and ICT project success. There are studies in the past that focused on negative leadership styles and their impact on project performance (Lategan and Fore, 2015; Pircher Verdorfer et al. , 2019; Schmid et al.…”
Section: Discussionmentioning
confidence: 99%
“…exploitative leadership as a moderator to the relationship between project governance and ICT project success. There are studies in the past that focused on negative leadership styles and their impact on project performance (Lategan and Fore, 2015;Pircher Verdorfer et al, 2019;Schmid et al, 2018), but exploitative leadership, being a newer concept, has never been explored as a negative contributor to project success in previous studies. This study has revealed the significant negative role of exploitative leadership in ICT project success.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…A leader's openness toward any change ensures prosperity and success for the organization and the workforce (Loyd-Walker and Walker, 2011). The attributes required by the leaders to provide successful delivery of the projects involve proper communication, plan oriented approach and a track record of and progress (Lategan, 2015).…”
Section: Relationshipsmentioning
confidence: 99%
“…It was found that project leadership had significant positive influence on project success. Lategan and Fore (2015) study examined the impact of leadership styles on project success: A Case of a telecommunications company. This study is descriptive in nature.…”
Section: Political Leadership and Project Successmentioning
confidence: 99%